REINTERPRETASI AYAT-AYAT AL-QUR’AN TENTANG DOMESTIC VIOLENCE - Siti Rohmah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2012)
Domestic Violence is an act of violence against women and violence in a family or marriage relationship. One argument that is often used, as the legitimacy and justification in the domestic violence is the Islamic teaching; it is especially the interpretation of verses of the Qur'an that present gender bias and discrimination against women. Therefore, reorientation and retraining of interpretation according to the nature of these teachings that are applicable and adaptive to changes in time and age are needed, without being followed by an interest or a particular interest.The straighten of interpretation would require honesty and sincerity of all parties. Thus, the followers of the teachings of Islam and spreaders will not be stucked in an explicit sense without understanding the meaning of the lines.